Pengaruh Kepemimpinan, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT MEGA MARINE PRIDE BEJI PASURUAN (Studi Kasus Pada Kinerja Karyawan PT MEGA MARINE PRIDE) - A, Ardy Saputra; Basalamah, Muhammad Ridwan; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract  This research was conducted at PT. MEGA MARINE PRIDE in Beji District. The type of research used in this research is quantitative research. The purpose of this research is to determine the influence of leadership, motivation and work environment on employee performance. The sample used in this research was 148 people as employees of PT Mega Marine Pride. Data collection techniques use questionnaires.The results of the research show that: 1) leadership, work motivation and work environment simultaneously influence employee performance. 2) Leadership variables have a significant positive effect on employee performance. 3) The motivation variable has a significant positive effect on employee performance. 4) Work environment variables have a significant positive effect on employee performance. Keywords: Leadership, Motivation, Work Environment, and Employee Performance